The Effectiveness of Percutaneous Balloon Compression, Thermocoagulation, and Glycerol Rhizolysis for Trigeminal Neuralgia in Multiple Sclerosis. Issue 4 (8th April 2019) - Noorani, Imran; Lodge, Amanda; Vajramani, Girish; Sparrow, Owen
Abstract: BACKGROUND: Balloon compression (BC), thermocoagulation (TC), and glycerol rhizolysis (GR) are percutaneous surgical options for trigeminal neuralgia (TN). Whether the outcomes of these procedures in multiple sclerosis -related TN (MS-TN) are as effective as in idiopathic TN (ITN) is unknown. OBJECTIVE: To retrospectively compare pain relief, complications, and durability achieved by these 3 types of procedures in MS-TN and ITN. METHODS: Two hundred and four patients with typical TN were treated percutaneously: 33 had MS-TN (64 procedures) and 171 had ITN (329 procedures). All were performed by 1 of 2 neurosurgeons; interviews enabled long-term data to be gathered by an independent observer. RESULTS: MS-TN patients (53.1%) had Barrow Neurological Institute pain scores of I or II after a percutaneous procedure, compared with 59.3% in the ITN cohort; there was no difference in initial relief between the 2 groups overall ( P  = .52). There was a trend toward fewer complications in MS-TN compared with ITN (23.4% vs 33.7%, respectively; P  = .058). Kaplan–Meier analysis demonstrated no difference in durability of relief in MS-TN (median 23.0 mo) compared with ITN overall (median 24.0 mo; P  = .75). Subgroup analysis demonstrated longer relief from BC and TC compared with GR in MS-TN ( P  = .013). Multivariate analysis confirmed that although the presence of MS does not predict durability of outcome, postoperative numbness ( P  = .0046) and undergoing a repeat procedure ( P  = .037) were significant predictors. CONCLUSION: BC and TC are safe and effective in MS-TN. Postoperative numbness is the strongest prognostic factor in MS-TN.